Qingda Granule Attenuates Angiotensin II-Induced Blood Pressure and Inhibits Ca2+/ERK Signaling Pathway - Wu, Meizhu; Wu, Xiangyan; Cheng, Ying; Shen, Zhiqing; Chen, Xiaoping; Xie, Qiurong; Chu, Jianfeng; Li, Jiapeng; Liu, Liya; Wei, Lihui; Long, Linzi; Cai, Qiaoyan; et al. (Frontiers in Pharmacology, 2021)
Objective: As a well-known Traditional Chinese Medicine formula prescribed by academician Ke-ji Chen, Qingda granule (QDG) lowered blood pressure and attenuated hypertensive cardiac remodeling and inflammation. However, its functional role and underlying mechanisms on hypertensive vascular function remains largely unclear. To assess the effects of QDG treatment on Angiotensin II (AngII)-induced hypertension and vascular function, as well as explore its underlying mechanisms both in vitro and in vivo. Methods: In vivo, 25 male C57BL/6 mice were randomly divided into five groups, including Control, AngII, AngII+QDG-L, AngII+QDG-M and AngII+QDG-H groups (n=5 for each group). Mice in AngII and AngII+QDG L/-M/-H groups were infused with AngII (500 ng/kg/min), while in Control group were infused with saline. Mice in AngII+QDG were administered intragastric with different concentrations of QDG (0.5725, 1.145 or 2.29 g/kg/day), while in Control and AngII groups were administered intragastric with equal volume of double distilled water for 2 weeks. Blood pressure was determined at 0-, 1- and 2-week of treatment. Ultrasound was used to detect the pulse wave velocity (PWV) and HE staining was used to detected the pathological change of abdominal aorta. RNA sequencing (RNA-seq) was performed to identify the differentially expressed transcripts (DETs) and related signaling pathways. IHC was used to detected the expression of p-ERK in abdominal aorta. VSMCs was used to assess the cellular Ca2+ release and activation of ERK pathway by confocal microscope and Western-Blotting analysis respectively. Results: QDG significantly alleviated the elevation blood pressure, the PWV and the thickness of abdominal aorta in AngII-induced hypertensive mice. RNA-seq and KEGG analysis identified 1505 DETs and multiple enriched pathways (including vascular contraction and calcium signaling pathway) after QDG treatment. Furthermore, confocal microscope showed that QDG partially attenuated the increase of Ca2+ release with the stimulation of AngII in cultured VSMCs. In addition, IHC and Western-Blotting indicated that QDG also partially alleviated the increase of phospho-ERK levels in abdominal aorta tissues of mice and VSMCs after the infusion or stimulation of AngII. Conclusion: QDG attenuated the elevation of blood pressure, abdominal aorta dysfunction and pathological changes, as well as Ca2+ release and activation of ERK signaling pathway.